News with artificial intelligence: Perception and Impact on Audiences and Professionals after a Radio Experiment - Terradillos, Julen Orbegozo (2025)
Purpose. This article analyses a pioneering radio experiment in the use of artificial intelligence (AI) conducted by the Basque public broadcaster in Basque, Euskal Irrati Telebista (EiTB), located in Spain. The initiative involved automating the generation of news texts and cloning human voices for news narration in the program Faktoria. Methodology. The research combines qualitative and quantitative methodologies to assess the detectability of automated content by the audience, as well as the perceptions and attitudes of listeners and media professionals towards the use of this technology. Results and conclusions. The results show that most listeners did not detect the presence of AI in the aired pieces, suggesting a high degree of technological mimicry. However, emotional values attributed to the automated voice, such as closeness and involvement, received lower ratings, indicating an emotional disconnection in the reception of AI-generated content. On a professional level, journalists expressed feelings of unease about the possibility of losing control over certain creative processes but also recognized the advantages of AI in automating routine tasks. Original contribution. This study is pioneering in evaluating the use of artificial intelligence in the creation of radio content in a minority language like Basque, with a particular focus on the detectability of the content and providing new insights into its impact on both audiences and professionals.